Prophylactic protection from lethal henipavirus disease mediated by Nipah-derived defective interfering particles is influenced by challenge virus strain and viral speciesResearch in context - Stephen R. Welch; Jessica R. Spengler; Jessica R. Harmon; JoAnn D. Coleman-McCray; Sarah C. Genzer; Katherine A. Davies; Teresa E. Sorvillo; Florine E.M. Scholte; Sergio E. Rodriguez; Joel M. Montgomery; Stuart T. Nichol; Christina F. Spiropoulou (EBioMedicine)
Summary: Background: Henipaviruses, including Nipah and Hendra viruses, are zoonotic pathogens that can cause severe respiratory and neurological diseases with high mortality rates in humans. Due to the severity of the disease, the high pandemic potential of these viruses, and the lack of approved treatments, the development of safe and effective medical countermeasures against henipaviruses is a critical priority. Methods: Here, we evaluate treatment efficacy of defective interfering particles (DIPs)—naturally occurring virus-like particles that lack substantial portions of the viral genome—against henipaviruses in the Syrian hamster model of disease. Findings: Prophylactic DIP treatment markedly reduced clinical signs and lethality in Syrian hamsters. Single or repeated pre-exposure regimens, starting up to 3 days before challenge, provided protection, while post-exposure treatment was ineffective. DIPs derived from NiV strain Malaysia were most effective against NiV Malaysia but also provided strong protection against the closely related NiV Bangladesh with certain regimens. However, these DIPs offered minimal or no protection against lethality from the more distantly related Hendra virus. Interpretation: Our data indicate efficacy of DIPs as a pre-exposure prophylactic for henipavirus infection and support a direct mechanism of viral inhibition. Funding: This work was partially supported by the DARPA INTERfering and Co-Evolving Prevention and Therapy (INTERCEPT) program (DARPA-BAA-16-35), CDC Emerging Infectious Disease Research Core Funds, an appointment to the Research Participation Program at the Centers for Disease Control and Prevention (CDC) administered by the Oak Ridge Institute for Science and Education through an interagency agreement between the U.S. Department of Energy and CDC (K.A.D., S.E.R.), and by NIAID 1R01AI151006 (T.E.S).